Asia's new regionalism - Frost, Ellen L. (Lynne Rienner Publishers, 2008)
As the political drive to establish closer ties among Asian governments continues to gain momentum, there has been much debate about the realities of Asian regionalism. Does the community-building activity in fact signal the birth of "Asia Major"? What are the obstacles to integration? And is integration actually a positive trend for the region - and for external actors? Sifting rhetoric from fact, Ellen Frost offers a nuanced analysis of the political, economic, and strategic issues at stake.A central theme in Asia's New Regionalism is the link between integration driven by governments for political and security reasons and integration fueled by ethnic, cultural, and economic ties. Frost's exploration of these sometimes mismatched dynamics also highlights critical implications for policies both in the region and globally.This book provides a nuanced analysis of the complexities of Asian regionalism.